Affordances of Knowledge Translation in Medical Education. (April 2015) - Onyura, Betty; Légaré, France; Baker, Lindsay; Reeves, Scott; Rosenfield, Jay; Kitto, Simon; Hodges, Brian; Silver, Ivan; Curran, Vernon; Armson, Heather; Leslie, Karen
<x xml:space="preserve">Abstract</x> Purpose Little is known about knowledge translation processes within medical education. Specifically, there is scant research on how and whether faculty incorporate empirical medical education knowledge into their educational practices. The authors use the conceptual framework of affordances to examine factors within the medical education practice environment that influence faculty utilization of empirical knowledge. Method In 2012, the authors, using a purposive sampling strategy, recruited medical education leaders in undergraduate medical education from a Canadian university. Recruits all had direct teaching and curricular development roles in either preclinical or clinical courses across the four years of the undergraduate curriculum. Data were collected through individual semistructured interviews on participants' use of empirical evidence, as well as the factors that influence integration of empirical knowledge into practice. Data were analyzed using thematic analysis. Results Fifteen medical educators participated. The authors identified both constraining and facilitating affordances of empirical medical education knowledge use. Constraining affordances included poor quality and availability of evidence, inadequate knowledge delivery approaches, work and role overload, faculty and student change resistance, and resource limitations. Facilitating affordances included faculty development, peer recommendations, and local involvement in medical education knowledge creation. Conclusions Affordances of the medical education practice environment influence empirical knowledge use. Developing strategies for effective knowledge translation thus requires careful assessment of contextual factors that can enable, constrain, or inhibit evidence use. Empirical knowledge use is most likely to occur among medical educators who are afforded rich, facilitative opportunities for participation in creating, seeking, and implementing knowledge.